Lactation Massage Training on Cadre Skills - Siti Nurjanah; Erinda Nur Pratiwi; Desy Widyastutik (Journal of Midwifery, 2020)
Background: One way to stimulate oxytocin with lactation massage can be important and beneficial because it is known to improve relaxation, reduce pain and stress, and very many other health benefits. Lactation massage effectively accelerates recovery and improves hormonal balance. Levels of prolactin and oxytocin increase to facilitate breastfeeding.Method: This research method uses quasi experimental design with one-group pretest-postest design model. The provision of lactation massage training using lactation massage booklets. Skill information data collection using the list of points. Data analysis using paired t-test. Data is processed by using software in computer program Statistical Product and Service Solution ( SPSS) for windows to facilitate data calculation.Result: The results of the analysis using paired T-Test to find out the effect of lactation massage training with the media booklet on cadre skills in performing lactation massage obtained p value of 0.000 (p<0.05) means there is an influence of lactation massage training on cadre skills about lactation massage.Conclusion: The conclusion of this study is that there is an influence of lactation massage training with media booklet on cadre skills in performing lactation massage.